Somatic and germline analyses of a long term melanoma survivor with a recurrent brain metastasis - Weiss, Sarah (BMC Cancer, 2015)
BACKGROUND: Median overall survival (OS) of patients with melanoma brain metastases (MBM) is usually 6 months or less. There are rare reports of patients with treated MBM who survived for years. These outlier cases represent valuable opportunities to study the somatic and germline factors that may have influenced patient outcome and led to extended survival. CASE PRESENTATION: Here we report the clinical scenario of a 67 year old man with a recurrent brain metastasis from melanoma who has survived over 12 years post-resection. We review the literature relating to clinical and molecular variables associated with long term survival post-brain metastasis. We present the somatic characteristics of this individual patient’s tumor as well as an analysis of inherited genetic variants related to immune function. The patient’s resected brain tumor is BRAF V600E mutated, NRAS wild type (WT), and TERT C250T mutated. The patient is a carrier of germline variants in immunomodulatory loci associated with prolonged survival. CONCLUSIONS: Our data suggest that genetic variants in immunomodulatory loci may partially contribute to this patient’s unusually favorable outcome and should not be overlooked. With further and future investigation, knowledge of inherited single nucleotide polymorphisms (SNPs) may provide clinicians with more individualized prognostic information for melanoma patients, with potential implications for surveillance strategies and therapeutic interventions.